Uncovering the Complexity of Customer Loyalty in Islamic Banks: The Relationship between Service Quality, Experience, and Brand Image through Customer Satisfaction - Laili, Silvia Nur; Hasan, Irmayanti (Institut Agama Islam Sunan Giri Ponorogo, 2024)
The Islamic banking sector in Indonesia, especially after the merger of Bank Syariah Indonesia (BSI) in 2021, has shown tremendous growth. However, maintaining customer loyalty remains a significant challenge in this competitive landscape, with various factors potentially affecting customer retention in Islamic banking. This study investigates the relationship between service quality, customer experience, and brand image on customer loyalty at BSI KCP Mojokerto Gajah Mada, with customer satisfaction as a mediating variable. This study uses a quantitative approach using a structured questionnaire distributed to 110 customers selected through purposive sampling. Data analysis was conducted using Partial Least Square Structural Equation Modeling (PLS-SEM) to test the direct relationship and mediation effects. The study findings reveal that service quality and brand image directly affect customer loyalty, while customer experience requires the mediation of customer satisfaction to affect loyalty. In particular, service quality is negatively correlated with loyalty when mediated through satisfaction. Customer satisfaction effectively mediates the relationship between brand image and loyalty as well as between customer experience and loyalty. This study demonstrates the complex nature of customer loyalty formation in Islamic banking, suggesting that banks should focus on maintaining consistent service quality while building a strong brand image and positive customer experiences.